Financial Inclusion and Economic Growth: Evidence in Asia - bin Abd Hishamuddin, Mohd Razuan; Mohammed, Rozita @Uji; Bujang, Imbarine (Malaysian Journal of Business and Economics (MJBE), 2019)
The importance of an inclusive financial system in countries had been highlighted in the policy circle and is the priority in many countries especially in developed countries. Financial inclusion is a provision of suitable, affordable and quality of financial services to all segments contributing towards balance economic growth and development. In this research, the study on financial inclusion and economic growth is pursued. Therefore, the main objective of this paper is to investigate the impact of financial inclusion towards the economic growth in the Asian countries. The sample data for this paper is using developing countries, frontier market and developed countries in the Asian region. In order to achieve the research objective, the researchers will be using the OLS regression model and FE/RE regression modal in the static panel data as the methodology with 7 years of time period. Moreover, there will also be analysis using the Panel ARDL in term of long-run relationship and short-run relationship. Thus, the general findings, the researchers suggest that having inclusive financial system have significant to reduce the income inequality and help to bust up the economic growth of the countries in the Asian region. Furthermore, the mediating of income inequality has influenced the relationship between financial inclusion and economic growth.